A House in Zambia. Recollections of the ANC and Oxfam at 250 Zambezi Road, Lusaka, 1967-97 - Palmer, Robin; Palmer, Robin (Gadsden Publishers, 2008)
This is a story about a house with a history and about the people who lived or worked there. It captures something of the spirit of the times in the worlds of politics and development, and it discusses the links which were established between Oxfam GB in Zambia and the African National Congress of South Africa.